2021
DOI: 10.1177/21676968211042111
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Depressive Symptoms, Physical Symptoms, and Sleep-Wake Problems From Before to During the COVID-19 Pandemic Among Emerging Adults: Inequalities by Gender, Socioeconomic Position, and Race

Abstract: The impact of the COVID-19 pandemic on emerging adults is of global concern. We examine changes in depressive symptoms, physical symptoms, and sleep-wake problems from before to during the pandemic among college students and examine inequalities by gender, socioeconomic status (SES), and race ( N = 263, 52% Black, 48% White, and 53% female). As compared to pre-pandemic levels, increases were evident in depressive symptoms, physical symptoms, and sleep problems. Females had greater increases than males in depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…It is also worth mentioning that some of the variables included in our study have been shown to be associated with a longitudinal increase in depression before and during the pandemic. In particular, some data suggest that being female ( Fuller-Rowell et al, 2021 ; Seens et al, 2021 ; but Ausín et al, 2021 ) and having experienced a greater number of stressors ( Leach et al, 2021 ) are related to a greater increase in depressive symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth mentioning that some of the variables included in our study have been shown to be associated with a longitudinal increase in depression before and during the pandemic. In particular, some data suggest that being female ( Fuller-Rowell et al, 2021 ; Seens et al, 2021 ; but Ausín et al, 2021 ) and having experienced a greater number of stressors ( Leach et al, 2021 ) are related to a greater increase in depressive symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Their lower level of readiness to accept negative emotions in their partners, caused by a higher level of stress and an uncertain situation, could cause general frustration, including frustration directed at their child’s crying. During the COVID-19 pandemic, more than 30% of adults reported clinically meaningful symptoms of anxiety and depression [ 38 , 39 ], which may lead to more harsh behaviors toward one’s own children. Nevertheless, the frustration towards crying is an irritation and blaming the baby for the situation is a parent-oriented reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, adopting such a perspective helps to avoid homogenising the impacts of disasters and the needs of those affected by them and instead allows for a deeper understanding of the ways that certain factors interact with each other to result in differentiated outcomes. For example, rather than viewing women as vulnerable upon the onset of the COVID-19 pandemic simply because they are women, researchers have taken a closer look at the ways that socioeconomic status [ 11 , 12 ], housing circumstances [ 13 , 14 ], ethnicity [ 15 , 16 ], and migration status [ 17 ] interact with gender to influence situational vulnerability and susceptibility to negative outcomes. According to Ref.…”
Section: Previous Researchmentioning
confidence: 99%
“…Other researchers, such as [ 11 ]; have emphasised the role that socioeconomic status has in exacerbating critical outcomes for women, both in terms of coping and in terms of overall mental wellbeing, noting that it can increase psychosocial stress and financial insecurity as a result of the pandemic due to low or lack of financial reserves. Similarly [ 12 ], have noted how, when socioeconomic status is accounted for, an increase in sleep problems globally can be observed, with women experiencing higher frequencies of sleep problems than men, in addition to higher rates of symptoms of depression. Furthermore [ 27 ], have also advocated for taking socioeconomic status into account when attempting to uncover the underlying factors behind gender disparities in COVID-19-related outcomes.…”
Section: Previous Researchmentioning
confidence: 99%